UPLC Separation and QTof–MS Identification of Major Alkaloids in Plumula Nelumbinis - Lin, Zongtao (Phytochem Anal, 2014)
INTRODUCTION: As an essential medicine and tea source in many countries, Plumula Nelumbinis potentially exerts its major biological activities through its alkaloids. However, its activities are not fully understood due to the lack of studies on its chemical components. OBJECTIVE: To establish an Ultra Performance Liquid Chromatography–Diode-Array Detector (UPLC–DAD) method, combined with an Electrospray Ionization–Quadrupole Time-of-flight Mass Spectrometry (ESI–QTof MS), for the separation and identification of Plumula Nelumbinis alkaloids. METHODS: The eluant from an UPLC separation of an ethanol extract of Plumula Nelumbinis was directly infused into an ESI–QTof MS system. Both positive and negative ion modes of ESI with low and high Collision Energy (CE) were used to obtain sufficient MS information. RESULTS: 21 alkaloids were tentatively identified based on their chromatographic characteristics, UV spectra, exact mass, MS fragments, and literature reports. They consist of 6 bis-1-benzyltetrahydroisoquinoline, 11 benzyltetrahydroisoquinoline (containing 2 glycoalkaloids and 2 quaternary ammoniums), 2 aporphine, one proaporphine, and one indole alkaloids. Eleven were identified in Plumula Nelumbinis for the first time and 7 were firstly reported in Nelumbo nucifera Gaertn. Five compounds, namely norcoclaurine-4′-O-glucoside, norcoclaurine-6-O-glucoside, isolotusine, 6-demethyl-4′-methyl-N-methylcoclaurine and N-norisoliensinine, were characterized and proposed as new compounds. CONCLUSION: The established UPLC–DAD–ESI–QTof–MS method is efficient for systematic identification of the alkaloids in Plumula Nelumbinis extract.